(3fHPI ef CMhGd GdQLGd GdeeOhMjf hGdePehejfs - (3GdcTejQj, eMeO eQGO Hf eMeO UGOb Hf eMeO Ydj Hf MjOQs
(3ChdgG (B:s
(3GdMeO ddg (B... (3agPg fHPI ef CMhGd GdQLGd GdeeOhMjf hGdePehejf eQJHI Ydi GdMQha eY JbOje GdChd aGdCSeGA hCSeGA GdBHGA hfMhgG fbdJ ef cJH gPG Gdaf hYdGeI GdNdGUI (B...s
(3BNQgG (B:s
... (3eMeO Hf aVjd Hf ZRhGf GdVHj KbI bG Ug O eMeO Hf GdbGSe Hf RcjG GdeMGRj CHh YHO Gddg GdShOGfj KbI Yeh Ug KbI ef CMUGHfG LT (B( ) (3Hf GdaVjd Hf jSGQ (B...s
(3JHUQI GdeDda (B:s
(3eMeO eQGO Hf Ydj GdcTejQj GdhGQO aj eYLe GdeDdajf (B3\710 (3ehdOg (B1057 (3hhaGJg (B1130 (3hbO PcQ UGMH GdPQjYI Cf fSNI YHO GdMSjf GdWgQGfj ef GdcJGH efShNI (B1078 (3adh cGf JGQjNgG ZdW dcGfJ JQLeI GdeDda gj GdePchQI aj GdehVY GdSGda aj GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdPQjYI (B10 \ 261s
(3GdPQjYI (B10 \ 261s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs